1993
DOI: 10.1177/030573569302100201
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception of Performance Manner in the Movements of Solo Musicians

Abstract: The study of music perception has focused almost exclusively on sound, ignoring the role of seeing the performer's body movements. Whilst anecdotes frequently refer to the importance of the performer's movements, there is scant psychological evidence to support this finding. The closest equivalent work in visual event perception research has shown that covert mental dispositions (for instance, an intention to deceive an observer) are specified in body movements, and therefore provide important information for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
317
1
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(354 citation statements)
references
References 8 publications
19
317
1
15
Order By: Relevance
“…Of course, the limitation of drawing conclusions from a single case must be born in mind when interpreting results. Yet, as previous research demonstrates the powerful effect performing musicians' bodily gestures can have on observer judgments of performance [16,18,23], increased anxiety-related nonverbal behaviors could have the undesired effect of reducing performance quality by detracting from optimal communication with the audience.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the limitation of drawing conclusions from a single case must be born in mind when interpreting results. Yet, as previous research demonstrates the powerful effect performing musicians' bodily gestures can have on observer judgments of performance [16,18,23], increased anxiety-related nonverbal behaviors could have the undesired effect of reducing performance quality by detracting from optimal communication with the audience.…”
Section: Discussionmentioning
confidence: 99%
“…De nombreuses études ont montré que la seule modalité visuelle des gestes ancillaires (sans l'écoute du son associé) pouvait s'avérer suffisante pour percevoir le style de la performance [Davidson 1993, Dahl 2007, Nusseck 2009. Ces gestes formeraient par eux même un véritable langage corporel [Dahl 2003], une représentation visuelle des courbes sonores propre à être décodée par le public [Jensenius 2009].…”
Section: Perception De La Modalité Visuelleunclassified
“…Cela est particulièrement vrai pour les instruments joués en posture debout (violon, clarinette...). Par exemple, [Davidson 1993] a pu mettre en évidence que l'expressivité des violonistes est davantage portée par la modalité visuelle que la modalité auditive. Des résultats similaires ont été trouvés pour les clarinettistes [Vines 2003] et les marimbistes (la marimba est un instrument percussif joué debout) [McClaren 1988, Broughton 2009].…”
Section: Perception De La Modalité Visuelleunclassified
“…As Platz and Kopiez (2012) revealed in a meta-analysis, visual information can contribute significantly to the overall evaluation of an audio-visual performance by about 0.5 standard deviations. A visible score or music stand might be an important visual component of a live music performance, along with clothing (Griffiths, 2008(Griffiths, , 2009, expressive movements and physical appearance (Davidson, 1993;Davidson & da Costa Coimbra, 2001;Tsay, 2013), attractiveness (Ryan & Costa-Giomi, 2004;Ryan, Wapnick, Lacaille, & Darrow, 2006), unconventional playing techniques (Lehmann & Kopiez, 2013), visible signs of engagement (Behne, 1994b), facial expressions (Thompson, Graham, & Russo, 2005;Thompson & Russo, 2007) and conductor gestures (Wöllner, 2008;Wöllner & Auhagen, 2008). In a study on the influence of first impressions on the audience's motivation to continue the performance evaluation, Platz and Kopiez (2013) showed that the visual cue of a score or music stand could very well have an influence on this process.…”
mentioning
confidence: 99%